A Design Model for Information Dissemination on the Pulo Traditional Village Tourism Area in the Booklets and Leaflets - Winoto, Yunus; Anwar, Rully Khairul; Khadijah, Ute Lies Siti (TEMALI : Jurnal Pembangunan Sosial, 2022)
This study aims to design and construct information dissemination of the Pulo Indigenous village tourism area in Garut Regency, West Java Province. The communication media used in information dissemination activities are in the form of booklets and leaflets. The method used in this study uses the action research method. The primary data sources in this study were the traditional head of Kampung Pulo and tourists who came to Kampung Pulo. The secondary data was obtained from literature studies and the tourism office of Garut Regency. The data collection technique is done through observation, interviews, and literature study. Based on the results of the study, it is known that from the identification stage it is known that one of the factors is the lack of recognition of the Pulo Traditional Village tourist area because tourism promotion has not been optimally carried out so far, therefore it is necessary to create a promotional media in the form of disseminating information on the Pulo traditional village tourism area. The communication media used are booklets and leaflets. From the design results, the information dissemination consists of a cover, a preface, a table of contents, and the content or contents of the promotion. From the results of trials and improvements to the design of information dissemination. After disseminating information, it shows that the existence of promotional media for the Kampung Pulo tourist area in the form of booklets and leaflets is beneficial in promoting the Kampung Pulo tourist area, especially for people living outside Garut Regency.